Erythema induratum – a clinical case report - Devesa, Nuno (2002)
The AA. present the case of a 48-year-old patient with skin lesions on both legs,initially diagnosed as erythema nodosum. Biopsy revealed erythema induratum. Theauthors present this case for its rarity and possible association with tuberculosis,although aetiology remains uncertain. In this case tuberculosis was not confirmed (only a positive tuberculin hypersensitivity reaction). Following a good response to goldcompounds, the question as to whether this drug has bactericidal action, arises.